TWITCH PARAMETERS IN TRANSVERSAL AND LONGITUDINAL BICEPS BRACHII RESPONSE - Boštjan Šimunič; Dejan Križaj; Marco Narici; Rado Pišot (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2015)
Assessment of the contractile properties of skeletal muscles is continuing to be an important issue and a difficult task methodologically. Longitudinal direction of skeletal muscle contraction blurs intrinsic muscle belly contractile properties with many factors. This study evaluates and explains contractile properties such as: delay time (Td), contraction time (Tc), half relaxation time (Tr) and maximal amplitude (Dm) extracted from twitch transversal response and compare them with torque response. In fifteen healthy males (age 23.7 ± 3.4 years) isometric twitch transversal and torque responses were simultaneously recorded during graded electrically elicited contractions in the biceps brachii muscle. The amplitude of electrical stimulation was increased in 5 mA steps from a threshold up to a maximal response. The muscles' belly transversal response was measured by a high precision mechanical displacement sensor while elbow joint torque was calculated from force readings. Results indicate a parabolic relation between the transversal displacement and the torque Dm. A significantly shorter Tc was found in transversal response without being correlated to torque Tc (r = -0.12; p > 0.05). A significant correlation was found between torque Tc and the time occurrence of the second peak in the transversal response (r = 0.83; p < 0.001). Electrical stimulation amplitude dependant variation of the Tc was notably different in transversal than in torque response. Td was similar at submaximal and maximal responses but larger in transversal at just above threshold contractions. Tr has a similar linear trend in both responses, however, the magnitude and the slope are much larger in the transversal response. We could conclude that different mechanisms affect longitudinal and transversal twitch skeletal muscle deformations. Contractile properties extracted from the transversal response enable alternative insights into skeletal muscle contraction mechanics.